Navigating P2Y12 inhibition in the labyrinth of cardio-oncology care: cangrelor bridging in patients with cancer - Ali, Abdelrahman; Jewani, Poonam; Bourdillon, Max; Koutroumpakis, Efstratios; Khalaf, Shaden; Charitakis, Konstantinos; Thompson, Kara; Marmagkiolis, Konstantinos; Deswal, Anita; Iliescu, Cezar (Frontiers in Cardiovascular Medicine, 2024)
Cangrelor, an intravenous P2Y12 platelet inhibitor, reduced the rate of ischemic events compared to oral P2Y12 inhibition, without significant increases in severe bleeding during percutaneous coronary intervention (PCI) as demonstrated by the CHAMPION-PHOENIX randomized controlled trial (RCT) (1). Additionally, cangrelor has been used off-label as bridging antiplatelet therapy in patients with PCI at high thrombotic risk who require early (within 3-6 months) interruption of their oral P2Y12 inhibitor therapy (2). Advancements in cancer therapy have improved patient survival rates, leading to an increased number of cardiac procedures, such as PCI, among patients treated for cancer. There is limited information on the utilization of cangrelor in patients with cancer, particularly in those with thrombocytopenia (3). We present a single-center case series of cangrelor bridging in patients with cancer and recent PCI that required temporary interruption of dual antiplatelet therapy (DAPT).A 69-year-old female with a past medical history (PMH) of IgA kappa multiple myeloma (MM) with a history of autologous stem cell transplant on maintenance lenalidomide, end-stage renal disease on peritoneal dialysis, saphenous venous thrombosis, and coronary artery disease (CAD) with recent non-ST segment elevation myocardial infarction (NSTEMI) had a PCI to the mid-left anterior descending artery (LAD) three months prior to presentation with melena and acute on chronic anemia (hemoglobin 5.6 gm/dl). The patient was taking both clopidogrel and apixaban prior to admission and was noted to have an aspirin allergy. On admission, both clopidogrel and apixaban were held due to concern for gastrointestinal (GI) bleeding. The patient underwent a coronary angiogram with optical coherence tomography (OCT), which revealed suboptimal apposition of the previously implanted LAD stent (by approximately 20%). The interventional cardiology team recommended the initiation of cangrelor (day three of admission)